1999
DOI: 10.1074/jbc.274.41.28966
|View full text |Cite
|
Sign up to set email alerts
|

The JNKK2-JNK1 Fusion Protein Acts As a Constitutively Active c-Jun Kinase That Stimulates c-Jun Transcription Activity

Abstract: c-Jun N-terminal protein kinase (JNK), a member of the mitogen-activated protein (MAP) kinase family, regulates gene expression in response to various extracellular stimuli. JNK is activated by JNK-activating kinase (JNKK1 and JNKK2), a subfamily of the dual specificity MAP kinase kinase (MEK) family, through phosphorylation on threonine (Thr) 183 and tyrosine (Tyr) 185 residues. The physiological functions of the JNK pathway, however, are not completely understood. A major obstacle is the lack of specific and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 61 publications
3
108
1
Order By: Relevance
“…CNBr peptide mapping (18) was chosen to identify the regions of Itch phosphorylated by JNK1, because it generates three readily identifiable cleavage products containing potential MAPK phosphorylation sites. To phosphorylate Itch by JNK1 in living cells, it was coexpressed in HEK293 cells with a constitutively active JNKK2-JNK1 fusion protein (19). Alternatively, Itch was incubated in vitro with recombinant JNKK2-JNK1 in the presence of ␥-labeled ATP.…”
Section: Resultsmentioning
confidence: 99%
“…CNBr peptide mapping (18) was chosen to identify the regions of Itch phosphorylated by JNK1, because it generates three readily identifiable cleavage products containing potential MAPK phosphorylation sites. To phosphorylate Itch by JNK1 in living cells, it was coexpressed in HEK293 cells with a constitutively active JNKK2-JNK1 fusion protein (19). Alternatively, Itch was incubated in vitro with recombinant JNKK2-JNK1 in the presence of ␥-labeled ATP.…”
Section: Resultsmentioning
confidence: 99%
“…However, these JNK upstream stimuli also activate other signaling pathways. To determine to what degree that the JNK activation plays a role, we next evaluated the effect of JNKK2-JNK1 fusion protein that exhibits constitutive JNK activity (Zheng et al, 1999). The JNKK2-JNK1 fusion protein is specific for the JNK pathway, and it does not activate either p38 or ERK (Zheng et al, 1999).…”
Section: Phosphorylation Of Nur77 By Mekk1and Its Regulation Of Nur77mentioning
confidence: 99%
“…To determine to what degree that the JNK activation plays a role, we next evaluated the effect of JNKK2-JNK1 fusion protein that exhibits constitutive JNK activity (Zheng et al, 1999). The JNKK2-JNK1 fusion protein is specific for the JNK pathway, and it does not activate either p38 or ERK (Zheng et al, 1999). Unlike JNK that exclusively resides in the cytoplasm, and upon activation translocates into the nucleus to phosphorylate its nuclear targets (Minden and Karin, 1997), the JNKK2-JNK1 fusion resided in both the nucleus and the cytoplasm (Figure 4).…”
Section: Phosphorylation Of Nur77 By Mekk1and Its Regulation Of Nur77mentioning
confidence: 99%
“…To test this scenario, Jurkat cells were stably transfected with a mammalian expression vector encoding MKK7-JNK1, because it has been shown that MKK7-JNK1 fusion protein linked via a short peptide can express profound JNK activity in the absence of any stimulus (18). Immunoblotting analysis revealed weak expression of MKK7-JNK1 fusion protein in the two individual stable transfectants tested, Jurkat-y1 and Jurkat-y2 (Fig.…”
Section: Jnk Inhibitors Induce Cell Cycle Arrest and Apoptosis And Inmentioning
confidence: 99%
“…Transfection of Plasmid and siRNAs into T-ALL Cells pcDNA3.1 MKK7-JNK1 was constructed according to a previous report (18) and verified by DNA sequencing. MKK7-JNK1 stable transfectants and mock control were generated by Lipofectamine 2000-mediated transfection of Jurkat cells with pcDNA3.1 MKK7-JNK1 and pcDNA3.1, respectively, and selected against neomycin (800 μg/mL).…”
Section: Cells and Micementioning
confidence: 99%